Mortality and functional outcomes in elderly adults treated surgically by hemiarthroplasty for femoral neck fractures - Ankush Ratanpal; Katapadi Ramachandra Kamath; Preetham Raj V Salian; Saiprasad Sarvothama Baliga; Rajendra Annappa; Sayak Banerjee (SAGE Open Medicine)
Background: Despite multiple studies, less recent literature and data regarding the mortality associated with hip fractures in the elderly population are available. Objectives: To assess the mortality data and functional outcomes of patients who underwent cemented and uncemented hemiarthroplasty in femoral neck fractures. To evaluate if preoperative (minimum 2 months) calcium and vitamin D supplement intake in patients affects postoperative mobilization with or without walker support. Methods: All patients aged 65 and above who underwent hemiarthroplasty for femoral neck fractures in our tertiary care center were included. Postoperative functional outcomes were determined using the Modified Harris Hip score and Oxford Hip score at 3, 6, and 12 months. The mortality of the procedures was assessed at 3, 6, and 12 months. Individuals who took both calcium and vitamin D supplements for at least 2 months before surgery were divided into two groups: those who did not take supplements and those who did. Results: We studied 110 patients above the age of 65 years. The postoperative mortality rate at 3, 6 months and 1 year postoperatively was found to be 3.6%, 4.7%, and 15.5% respectively. Functional outcomes were assessed at 3, 6, and 12 months postoperatively using modified Harris Hip score and Oxford Hip score and were found to be identical in both cemented and uncemented hemiarthroplasty groups. Patients who took calcium and vitamin D supplements preoperatively (minimum 2 months) could walk without support at the end of 1-year post-surgery. Conclusion: Early surgery and early mobilization should be the main aim of treatment for femoral neck fractures.